Physiological adjustments and transcriptome reprogramming are involved in the acclimation to salinity gradients in diatoms. (27th June 2016) - Bussard, Adrien; Corre, Erwan; Hubas, Cédric; Duvernois‐Berthet, Evelyne; Le Corguillé, Gildas; Jourdren, Laurent; Coulpier, Fanny; Claquin, Pascal; Lopez, Pascal Jean
Summary: Salinity regimes in estuaries and coastal areas vary with river discharge patterns, seawater evaporation, the morphology of the coastal waterways and the dynamics of marine water mixing. Therefore, microalgae have to respond to salinity variations at time scales ranging from daily to annual cycles. Microalgae may also have to adapt to physical alterations that induce the loss of connectivity between habitats and the enclosure of bodies of water. Here, we integrated physiological assays and measurements of morphological plasticity with a functional genomics approach to examine the regulatory changes that occur during the acclimation to salinity in the estuarine diatom Thalassiosira weissflogii . We found that cells exposed to different salinity regimes for a short or long period presented adjustments in their carbon fractions, silicon pools, pigment concentrations and/or photosynthetic parameters. Salinity‐induced alterations in frustule symmetry were observed only in the long‐term (LT) cultures. Whole transcriptome analyses revealed a down‐regulation of nuclear and plastid encoded genes during the LT response and identified only a few regulated genes that were in common between the ST and LT responses. We propose that in diatoms, one strategy for acclimating to salinity gradients and maintaining optimal cellular fitness could be a reduction in the cost of transcription.